1807 Laws of Kentucky 1, An Act to Amend an act titled "An Act Concerning the Militia," ch. 1 § 3. - (:unkn) unknown (General Publisher, 1807)
imposed a fine of up to fifty cents on each non commissioned officer and private appearing on parade without a gun after being duly notified.
--
Keywords: ARMED FORCES